PROJEK LINGKUNGAN INKLUSIF (PROKLIN) DI SMPN 1 BATU LAYAR - Ramdhan, Aldi Putra; Soemardiawan, Soemardiawan; Widiyantoro, Setyo Putra; Dedy, Dedy (COMMUNITY : Jurnal Pengabdian Kepada Masyarakat, 2025)
ABSTRACT The issue at SMPN 1 Batu Layar, a model Go Green school, arises from the presence of scattered organic and non-organic waste, which undermines its image as an environmentally friendly school. This study aims to examine the benefits of the Inclusive Environmental Program (PROKLIN) in raising awareness and participation among school members in maintaining cleanliness and environmental sustainability. PROKLIN is expected to serve as a model for other schools in creating a clean, healthy, and sustainable school environment. The methods used in this activity include stages of socialization and workshops on waste processing, followed by assistance in the implementation of the Inclusive Environmental Program (PROKLIN). This program aims to increase the awareness and participation of the school community in maintaining the cleanliness and sustainability of the school environment. The final stage is the evaluation of the program to assess the effectiveness and impact of the activities carried out. The community service results show an improvement in students’ understanding and skills in managing organic and non-organic bottle waste through several activity stages. The findings also indicate that PPG UNDIKMA students were not only able to effectively practice bottle waste processing but also experienced positive changes in daily behavior related to the implementation of a sustainable lifestyle and the Go Green movement at school and in the surrounding environment. This activity also supports the development of the Pancasila student profile, especially in aspects of mutual cooperation (gotong royong), environmental care, and independence. ABSTRAK Permasalahan di SMPN 1 Batu Layar sebagai sekolah percontohan Go Green muncul akibat banyaknya sampah organik dan nonorganik yang berserakan, sehingga mengganggu citra sekolah ramah lingkungan. Penelitian ini bertujuan untuk mengetahui manfaat Program Lingkungan Inklusif (PROKLIN) dalam meningkatkan kesadaran dan partisipasi warga sekolah dalam menjaga kebersihan dan kelestarian lingkungan. PROKLIN diharapkan menjadi model bagi sekolah lain dalam menciptakan lingkungan yang bersih, sehat, dan berkelanjutan. Metode yang digunakan dalam kegiatan ini mencakup tahapan sosialisasi dan workshop pengolahan sampah, diikuti dengan pendampingan dalam pelaksanaan Program Lingkungan Inklusif (PROKLIN). Program ini bertujuan untuk meningkatkan kesadaran dan partisipasi warga sekolah dalam menjaga kebersihan dan kelestarian lingkungan sekolah. Tahapan terakhir adalah evaluasi program untuk menilai efektivitas serta dampak dari kegiatan yang telah dilaksanakan. Hasil pengabdian menunjukkan peningkatan pemahaman dan keterampilan siswa dalam pengelolaan limbah sampah botol organik maupun nonorganik melalui beberapa tahapan kegiatan. Temuan juga mengindikasikan bahwa mahasiswa PPG UNDIKMA tidak hanya mampu mempraktikkan pengolahan sampah botol secara efektif, tetapi juga mengalami perubahan positif dalam perilaku sehari-hari terkait penerapan gaya hidup berkelanjutan dan gerakan Go Green di sekolah maupun lingkungan sekitarnya. Kegiatan ini turut mendukung pembentukan profil pelajar Pancasila, khususnya dalam aspek gotong royong, kepedulian terhadap lingkungan, dan kemandirian.